S.A.L.A.M. AN INCLUSIVE SENSORY INTERVENTION FRAMEWORK WITHLEGO, ART AND MOOD BOARD FOR SPECIAL NEEDS STUDENTSIN MALAYSIAN CLASSROOM (Proceedings of International Conference on Special Education, 2025)
Previous studies had highlighted that special need individuals have unique sensory sensitivity and may perceive stimulation towards sensory differently, which may lead to maladaptive behaviours and emotions when experiencing sensory discomfort. This phenomenon may also be observed in the classroom setting of special need students, as some of them may have difficulties in adapting to the physical and social conditions. A Multi-Sensory Environment was commonly used in special-needs school, however empirical investigations into how to best use this facility and its effectiveness was limited, especially in Malaysian setting. To address some of the challenges that the students encountered, a specially designed area and integrated with LEGO, art and Mood Board approaches were introduced in a classroom setting to the students. The area was named as S.A.L.A.M., which is an acronym for Sensory Area with Lego, Art and Mood Board. Specific activities were conducted in the S.A.L.A.M. and the Completion of Activity Response Evaluation (CARE), was administered to all the students who participated in the activities. It was acknowledged that students enjoyed the learning processes of the S.A.L.A.M., and they had better understanding of their physical and psychological status when experiencing disturbance in life. Through the activities, it was observed that they become more confident and calmer towards distractions and learned to have more positive behavioural reaction. As a conclusion, the introduction of SALAM in classroom setting for special need students may provide the unique conditions for learning and valuable opportunity for them to live and develop to their maximum potential in education and life.